2008
DOI: 10.1007/s00468-008-0222-y
|View full text |Cite
|
Sign up to set email alerts
|

Wood anatomy and hydraulic architecture of stems and twigs of some Mediterranean trees and shrubs along a mesic-xeric gradient

Abstract: Woody species populating the major Mediterranean ecosystems in the world are characterized by different levels of adaptation to the seasonal Mediterranean climate conditions. Many species of these ecosystems show wood features that allow high efficiency of transport when water is available, while maintaining hydraulic safety during drought periods. This study focuses on the anatomy of juvenile and mature wood of some species representative of continuous sequences of Mediterranean vegetation formations accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
54
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(62 citation statements)
references
References 69 publications
6
54
1
1
Order By: Relevance
“…Such adjustments in hydraulics enabled trees in arid areas to have a higher sap flux density and stomatal conductance than the same species in mesic areas, particularly when the vapor pressure deficit was low [27,65]. Thus, trees in arid areas would be able to sequester substantial amounts of carbon while environmental conditions were favorable, such as during the morning hours prior to stomatal closure [12,13,[68][69][70][71][72]. Shorter tree height during water shortages ( Figure 3A,C) would be beneficial for the survival of Siberian elm under dry conditions, not only by decreasing the risk of wind fall, especially in the high windy areas of the Mongolian desert, but also by changing the hydraulic characteristics of trees.…”
Section: Height and Dbhmentioning
confidence: 99%
“…Such adjustments in hydraulics enabled trees in arid areas to have a higher sap flux density and stomatal conductance than the same species in mesic areas, particularly when the vapor pressure deficit was low [27,65]. Thus, trees in arid areas would be able to sequester substantial amounts of carbon while environmental conditions were favorable, such as during the morning hours prior to stomatal closure [12,13,[68][69][70][71][72]. Shorter tree height during water shortages ( Figure 3A,C) would be beneficial for the survival of Siberian elm under dry conditions, not only by decreasing the risk of wind fall, especially in the high windy areas of the Mongolian desert, but also by changing the hydraulic characteristics of trees.…”
Section: Height and Dbhmentioning
confidence: 99%
“…Further related to drought resistance, De Micco et al (2008) reported a gradual adaptation in different Mediterranean trees and shrubs species to severe drought periods after evaluating their wood anatomical traits along a mesic-xeric gradient. However, how these strategies and xylem features, including resistance to embolism, vary between co-existing Mediterranean species but within a single genus has been poorly evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly Ref. [69] conducted a study focussing on the anatomy of juvenile and mature wood of some species representative of continuous sequences of Mediterranean vegetation formations according to gradients of water availability, from xeric to relatively mesic. The difference between juvenile and mature structures was large in the species of the mesic end of the gradient while it was relatively small in those more xeric, vessels were narrow resistant to cavitation during drought and freezing conditions.…”
Section: Wood Anatomymentioning
confidence: 99%
“…The difference between juvenile and mature structures was large in the species of the mesic end of the gradient while it was relatively small in those more xeric, vessels were narrow resistant to cavitation during drought and freezing conditions. A study was undertaken on the seasonal dimorphism in wood anatomy [69] in Mediterranean sub sp. Cistus incanus revealed that brachyblast wood was safer than dolichoblast and has narrower and more frequent vessels.…”
Section: Wood Anatomymentioning
confidence: 99%
See 1 more Smart Citation